Modern approaches of detecting financial statement fraud - Tkachenko Liudmila; Andrey Erisov; Pozdeeva Galina; Romanyuk Vera (SHS Web of Conferences, 2020)
The paper considers the modern methods for detecting financial statement errors and fraud with respect to their application to Russian corporate companies. The study methods evaluating the financial statements of companies allow getting a comprehensive and quick assessment of the financial condition of the company based on open sources. An assessment of the financial statements of enterprises according to the Roxas model showed that the composite index of the model is applicable to Russian companies.